Abstract 107: Patterns, determinants and long term outcomes of hyperglycemia among subjects recovering from COVID 19 illness - Jamwal, Juhi; Ganaie, Ashraf; Shah, Sonaullah; Qadri, Syed (Indian journal of endocrinology and metabolism, 2022)
Objectives: While presence of diabetes has been frequently associated with severe Corona virus Disease 2019 (COVID-19) caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARSCoV-2), new onset hyperglycemia had been common phenomenon seen in these patients and associated with poor outcomes. Less is known about determinants of this and its long-term outcomes. Materials and Methods: This were a retrospective and prospective hospital based; observational study and a total of 302 patients who suffered from COVID 19 illness from January 2021 to January, 2022 were included after fulfilling inclusion criteria and procuring informed consent. Patients with diabetes mellitus were excluded from the study. Hyperglycemia was defined as BGF 3 126 mg/dl or BGR 3 200 mg/dl or Hba1c 36.5% on admission or anytime during hospital stay. Results: Average age of study population was 51.82 ± 18.33 years and male to female ratio was 1.7:1. Out of 302 patients, 40 had mild disease and 262 had moderate to severe disease. 27 patients developed hyperglycemia during their admission and all the patients had suffered severe COVID 19 illness. They were managed with Insulin therapy. One patient had presented with Diabetic ketoacidosis and later diagnosed with Type 1 diabetes mellitus. The major determinants of hyperglycemia were age, BMI, Severity of illness, use of steroids especially methylprednisolone and family history of diabetes. On follow up at 1 year, no new appearance of hyperglycemia was seen in euglycemic subjects and 6 out of 27 patients persisted with diabetes and were managed with oral antidiabetics. Conclusion: The incidence of new onset diabetes is increased in patients with COVID 19 however, the mechanism of how SARS-CoV-2 might lead to incident diabetes is likely complex and could differ by type 1 and type 2 diabetes. Monitoring of long-term metabolic consequences of COVID 19 illness including Diabetes mellitus is required.